Theory of Change Analysis: Building Robust Theories of Change - and Mayne, John (Canadian Journal of Program Evaluation, 2017)
Models for theories of change vary widely as do how they are used. What constitutes a good or robust theory of change has not been discussed much. This article sets out and discusses criteria for robust theories of change. As well, it discusses how these criteria can be used to undertake a vigorous assessment of a theory of change. A solid analysis of a theory of change can be extremely useful, both for designing or assessing the designs of an intervention as well as for the design of monitoring regimes and evaluations. The article concludes with a discussion about carrying out a theory of change analysis and an example.